203k views
1 vote
Show that n+1C = nCr-1 + nr.

User Pmoubed
by
5.8k points

1 Answer

4 votes

Answer: The proof is given below.

Step-by-step explanation: We are given to show that the following equality is true :


^(n+1)C_r=^nC_(r-1)+^nC_r.

We know that

the number of combinations of n different things taken r at a time is given by


^nC_r=(n!)/(r!(n-r)!).

Therefore, we have


R.H.S.\\\\=^nC_(r-1)+^nC_r\\\\\\=(n!)/((r-1)!(n-(r-1))!)+(n!)/((r)!(n-r)!)\\\\\\=(n!)/((r-1)!(n-r+1)!)+(n!)/((r)!(n-r)!)\\\\\\=(n!)/((r-1)!(n-r+1)(n-r)!)+(n!)/(r(r-1)!(n-r)!)\\\\\\=(n!)/((r-1)!(n-r)!)\left((1)/(n-r+1)+(1)/(r)\right)\\\\\\=(n!)/((r-1)!(n-r)!)\left((r+n-r+1)/((n-r+1)r)\right)\\\\\\=(n!)/((r-1)!(n-r)!)*(n+1)/((n-r+1)r)\\\\\\=((n+1)!)/(r!(n-r+1)!)\\\\\\=((n+1)!)/(r!((n+1)-r)!)\\\\\\=^(n+1)C_r\\\\=L.H.S.

Thus,
^(n+1)C_r=^nC_(r-1)+^nC_r.

Hence proved.

User Brent Chapman
by
6.0k points